Mesin Penghancur Cangkang Kerang - Muh. Rizal Ode; Lukas Kano Mangalla; Aminur; Erick Patollong (Piston: Jurnal Teknologi, 2023)
Along with the increasing demand for clam meat, this causes the waste of clam shells to accumulate and not be utilized which can pollute the environment and its surroundings. The purpose of this research is to design and manufacture a shell crusher machine. The working principle of this shell crusher machine is that the crushing process is carried out by inserting the shells into the inlet which is crushed by the blade, then utilizing a gasoline motor as the main drive, where the rotation of the machine is continued by a series of main shafts consisting of blades, shafts, bearings, v-belts and pulleys, as the main components of the design of a shell crusher machine so that it can be processed to be used as animal feed and organic fertilizer which is good for plant health. From the results of the design and manufacture of this shell crusher tool it can crush every 1 kg of shellfish in 1 minute 53 seconds.